Tuning the adsorption of perylene-based surfactants on the surface of single-walled carbon nanotubes - Backes, Claudia; Hauke, Frank; Hirsch, Andreas; Hauke, Frank (physica status solidi (b), 2013)
Despite tremendous progress in dispersion and sorting of carbon nanotubes using surfactant systems in water, the effect of the surrounding aqueous medium is only poorly understood. Herein we present a study on the effect of pH and ionic strength on the adsorption behavior of surfactants on the SWCNT scaffold and the related differences in dispersion and individualization. We have turned to an anionic perylene bisimide dye as model surfactant, as the rich spectroscopy allows us to trace the interaction with and the packing densities on the SWCNTs. We show that higher ionic strength and high packing density is beneficial for the dispersion yield, while high net charge density on the surface is the crucial factor for exfoliation. The accessible tuning of the packing densities furthermore enabled the investigation of preferential interaction of the dye with certain nanotube species. Environmental effects: crucial factors for nanomaterial dispersion and exfoliation as demonstrated with the aid of a nanotube-perylene bisimide model system. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.